2011
DOI: 10.1371/journal.pone.0022901
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Plays a Crucial Role in Inhibiting Neuronal Differentiation of Neural Stem/Progenitor Cells via VEGF Signaling-Dependent Pathway

Abstract: In the present study, we aim to elucidate the roles of caveolin-1(Cav-1), a 22 kDa protein in plasma membrane invaginations, in modulating neuronal differentiation of neural progenitor cells (NPCs). In the hippocampal dentate gyrus, we found that Cav-1 knockout mice revealed remarkably higher levels of vascular endothelial growth factor (VEGF) and the more abundant formation of newborn neurons than wild type mice. We then studied the potential mechanisms of Cav-1 in modulating VEGF signaling and neuronal diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 70 publications
3
24
0
Order By: Relevance
“…Caveolin‐1 KO mice exhibit signs of premature neuronal aging and degeneration in the hippocampus, which is similar to what is found in AD; thus, down‐regulation of Cav‐1 may accelerate aging and neurodegeneration (Head et al, 2010). Previous studies have shown that overexpression of caveolin‐1 can promote astroglial differentiation of NPCs, which enhances the Notch signaling pathway (Li et al, 2011a,b). The Notch signaling pathway is highly conserved and plays a crucial role in regulating stem cell proliferation, differentiation, apoptosis, neurogenesis and neuronal differentiation (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Caveolin‐1 KO mice exhibit signs of premature neuronal aging and degeneration in the hippocampus, which is similar to what is found in AD; thus, down‐regulation of Cav‐1 may accelerate aging and neurodegeneration (Head et al, 2010). Previous studies have shown that overexpression of caveolin‐1 can promote astroglial differentiation of NPCs, which enhances the Notch signaling pathway (Li et al, 2011a,b). The Notch signaling pathway is highly conserved and plays a crucial role in regulating stem cell proliferation, differentiation, apoptosis, neurogenesis and neuronal differentiation (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, cav-1 inhibits the activity of flk-1, the receptor of VEGF, potently inhibiting VEGF-dependent angiogenesis. 21 In addition, vasodilatation and increased permeability of blood vessels, mediated by nitric oxide, constitutes an important mechanism for angiogenesis. Nitric oxide synthase (NOS) in vascular endothelial cells is located within caveolae and the caveolin scaffolding domain of cav-1 can combine with NOS making it inactive and, thereby, inhibiting angiogenesis.…”
Section: Caveolin-1 Expression and Clinical Severity In Psoriasis Vulmentioning
confidence: 99%
“…VEGF secretion promotes the self-renewal of NSCs and brain development, and it has been found to confer protection from cerebral ischemia [22]. Previous reports have suggested that infusion of VEGF into the lateral ventricle increases neurogenesis by promoting survival of newborn neurons and NSCs [23], [24].…”
Section: Discussionmentioning
confidence: 99%